Educational Resilience and Effective Support Systems in Times of Socio-Economic Uncertainty - Felicia Ofuma Mormah (Siber International Journal of Digital Business (SIJDB), 2026)
The issue of educational resilience has been of paramount concern in the current educational systems, especially in those settings where there is socio-economic insecurity. This paper discusses the role of integrated support systems in enhancing the resilience of students and boosting learning outcomes in the face of financial and psychological stress, as well as structural inequities. The research design chosen is a document review research design, which utilizes the available scholarly literature, policy reports and institutional documents to synthesize existing knowledge on the topic of educational resilience and support mechanisms. The analysis is based on critical areas of support systems, such as financial support programmes, counseling and psychosocial interventions, trauma-sensitive education, teacher training, and community-based interventions. The results suggest that the best practices to promote educational resilience are holistic and coordinated strategies that meet the academic, emotional and social requirements at the same time. Financial interventions like student loan schemes, bursaries, and counseling and trauma-informed practices can boost access and retention, as well as the psychological well-being and engagement in learning of students. The research also shows that the interventions that are fragmented or isolated can no longer be effective in maintaining long-term resilience in learners. The research finds that sustainable educational resilience is a need that necessitates combined policy frameworks, ongoing educator development, and properly designed support systems that facilitate equity and inclusion. Strategies include enhancing the institutional coordination, increasing access to financial support, and institutionalization of psychosocial support services so that learners can succeed in spite of socio-economic uncertainty.